MANAJEMEN KURIKULUM PADA PENDIDIKAN SMP SATU ATAP DI KABUPATEN MURUNG RAYA - Aprianto (Pendidikan Dasar - Pascasarjana Universitas Negeri Jakarta, 2021)
This research aims to improve students' creative thinking skills and student learning outcomes of class VI Bakalan Elementary School in science learning through a project-based learning model. The research subjects were 15 students consisting of 10 male students and 5 female students. This research was conducted in the even semester of the 2020/2021 academic year. This type of research used is Classroom Action Research. The data were collected by means of interviews, observations, and tests. The data analysis techniques used were qualitative and quantitative. Based on the results of this research, it shows that the project-based learning model can improve students' creative thinking skills and science learning outcomes in science learning content in class VI A of Bakalan Elementary School. Based on the results of data analysis, there was an increase in students' creative thinking skills starting from the pre-cycle stage to cycle 2, which initially the average creative thinking ability of students was 26% to 78%. The average creative thinking skills of students in one class increased 52%. Student learning outcomes also increased, based on preliminary data from pre-cycle to cycle 2.The average completeness of student learning outcomes in the pre-cycle stage was 13% to 73% in cycle 2. Average of science learning outcomes of class VI A students increased 60%.